Answer:
2H2S(g) + 3O2(g) → 2H2O(g) + 2SO2(g) + 248kcal
Step-by-step explanation:
The reaction of the problem occurs as follows:
H2S(g) + O2(g) → H2O(g) + SO2(g)
To balance the reaction we must balance oxygens:
H2S(g) + 3O2(g) → 2H2O(g) + 2SO2(g)
To balance the complete reaction:
2H2S(g) + 3O2(g) → 2H2O(g) + 2SO2(g)
As the energy is evolved, 124kcal are as product in the reactio per mole of H2S. As the balanced reaction contains 2 moles of H2S, the heat evolved is:
124kcal*2 = 248kcal:
2H2S(g) + 3O2(g) → 2H2O(g) + 2SO2(g) + 248kcal
And this is the balanced equation